STUDI TANAMAN BERKHASIAT OBAT SUKU MORI DI KECAMATAN PETASIA, PETASIA BARAT, DAN PETASIA TIMUR KABUPATEN MOROWALI UTARA SULAWESI TENGAH - Idris Idris; Nurlina Ibrahim; Arsa Wahyu Nugrahani (Biocelebes, 2018)
This study aims to conduct an inventory, knowing how to use and organs of plants used as medicine by Mori Tribal in Petasia, Petasia and East Petasia District, West North Morowali Regency of Central Sulawesi. This study used qualitative methods and sampling techniques that snowball sampling, with open-ended interview techniques interview on media 9 informants obtained using a questionnaire. Based on the results of research known as 79 species of medicinal plants, 2 of which can not be identified and divided into 45 familia used as a medicine. Plants are most widely used is of familia Euphorbiaceae as many as 8 species. Organs of plants used include leaves, stems, fruits, rhizomes, seeds, bark, flowers, bulbs, herbaceous roots and sap. Organ plant is widely used is the leaves that percentage utilization is 58%. Mori Tribal communities in the District, West Petasia and East Petasia North Morowali District use medicinal herbs to treat the disease, healing and health maintenance. The cooking methods include boiling water, brewed, boxed, taped, squeezed, scrubbed/smeared, chewed and consumed directly, drops, and sprayed. How to use include drunk, eaten, chewed and consumed directly, polished/smeared, attached, dropped, and chewed and sprayed on the affected area.